The tiny hero of Ferny Creek Library - Bailey, Linda, 1948- (Greenwillow Books, an imprint of HarperCollinsPublishers, 2017)
When Aunt Min disappears, Eddie the bug leaves the classroom where his family lives to try to find her, then helps save their beloved school library from budget cuts.